Challenges in the Physical Characterization of Lipid Nanoparticles - Supandeep Singh Hallan; Maddalena Sguizzato; Elisabetta Esposito; Rita Cortesi (Pharmaceutics, 2021)
Nano-sized drug transporters have become an efficient approach with considerable commercial values. Nanomedicine is not only limited to drug delivery by means of different administration routes, such as intravenous, oral, transdermal, nasal, pulmonary, and more, but also has applications in a multitude of areas, such as a vaccine, antibacterial, diagnostics and imaging, and gene delivery. This review will focus on lipid nanosystems with a wide range of applications, taking into consideration their composition, properties, and physical parameters. However, designing suitable protocol for the physical evaluation of nanoparticles is still conflicting. The main obstacle is concerning the sensitivity, reproducibility, and reliability of the adopted methodology. Some important techniques are compared and discussed in this report. Particularly, a comparison between different techniques involved in (a) the morphologic characterization, such as Cryo-TEM, SEM, and X-ray; (b) the size measurement, such as dynamic light scattering, sedimentation field flow fractionation, and optical microscopy; and (c) surface properties, namely zeta potential measurement, is described. In addition, an amperometric tool in order to investigate antioxidant activity and the response of nanomaterials towards the skin membrane has been presented.